Analysis of Landscape Architecture Planning and Design Under the Background of Multimedia Based on Swarm Intelligence Optimization Path Algorithm (Informatica, 2024)
Computer technology has brought greater convenience and effect to landscape architecture design. A multimedia-based landscape architecture method based on the optimization calculation method of swarm intelligence is proposed in this paper. Composition is performed through creation of the environment for the landscape architecture; then the landscape architecture processing in the basic classic multimedia environment is compared and analyzed; meanwhile updated methods are provided. The experimental results prove that compared with the traditional way of calculation and planning, the calculation method using the swarm intelligence optimization path has a smaller comparison of path length and can meet the design and planning standards of landscape architecture.